Renate Lachmann: Im Lager der Literatur - Hansen-Löve, Aage A. (Wiener Slawistischer Almanach, 2025)
The essay reviews Renate Lachmann’s book Lager und Literatur: Zeugnisse des GULAG (Camp and Literature, 2019) and contextualizes it within Lachmann’s previous literary and cultural studies.